The trade effect of the EU's preference margins and non-tariff barriers - Maria Cipollina; Federica De Maria (Journal of Risk and Financial Management, 2020)
Nowadays, trade negotiations afford both liberalism- and protectionism-oriented policies. Indeed, in recent decades, the developed countries have been actively engaged in negotiating many preferential agreements to integrate developing countries (DCs) into world trade and encourage their economic growth, but many of these schemes contrast with the complex rules, often imposed on international markets, that still are an obstacle for exporters. Their presence and related costs reduce the importance of preferential trade agreements (PTAs) in increasing trade flows. This article attempts to assess the impact of preferential trade policies on trade flows controlling for different non-tariff barriers (NTBs), using a structural gravity model. The analysis uses disaggregated data, registered in the year 2017, on EU imports (defined at level HS-6 digit) from a large number of exporters (187 developed and developing countries) and also includes the intra-EU trade. Our results show robust and positive estimates for the impact of preferences on bilateral trade flows, however, higher non-tariff barriers are likely to play a role in reducing both the extensive margins of trade, and so tariff preferences alone are not sufficient to access international markets. The impact of NTBs on the intensive margin of trade is ambiguous; some measures may act as catalysts and therefore increase trade, and others may act as an additional cost of trade and thus hinder trade.
Keywords: F13; F14; Q17; 330; gravity model; hierarchical regression; non-tariff barriers; Poisson estimator; preferential margins; trade policy